Biomechanical data - Potthast, W. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
Before initiating sports technology interventions for performance enhancement or injury prevention, the determinant factors or risk factors must be known. If this knowledge is based on empirical work or experience, technologies can be developed, e.g. for performance enhancement. The interaction of the athlete with the technological tool is of particular importance here. This interaction can be based more on performance-physiological mechanisms (respiratory-cardiovascular-metabolic) or optimize neuromuscular-skeletal functions.